Sexually Transmitted Infections Among Kenyan Adolescent Girls and Young Women With Limited Sexual Experience - Yuh, Tiffany; Micheni, Murugi; Selke, Stacy; Oluoch, Lynda; Kiptinness, Catherine; Magaret, Amalia; Chohan, Bhavna; Ngure, Kenneth; Wald, Anna; Mugo, Nelly R.; Roxby, Alison C. (Frontiers in Public Health, 2020)
Objectives Globally, the highest rates of sexually transmitted infections (STIs) are among the 15-24 age group. Studying adolescent girls and young women (AGYW) pre-sexual debut could identify risk factors for STI acquisition. Methods We recruited a prospective cohort of low-risk AGYW aged 16-20 in Kenya. Participants were HIV and HSV-2 seronegative and reported no history of sexual intercourse or reported sex with one partner. Participants underwent genital exams, nucleic acid testing of vaginal swabs for Neisseria gonorrhea (NG), Chlamydia trachomatis (CT), Trichomonas vaginalis (TV), and vaginal gram stains for vaginal dysbiosis by Nugent score. STI correlates were described using χ2 test and t-test. Results We enrolled 400 AGYW, of which 322 (80.5%) reported never having had sex, while 78 (19.5%) reported prior sex with 1 partner. Among the 78 participants reporting prior sex, 20 (25.6%) reported contraception use in the last 3 months, with 60% using only emergency contraceptive pills. Despite self-reported history, of 373 subjects who underwent STI testing, 49 subjects (13.1%) tested positive for STIs, with 41 CT, 5 GC, and 3 TV cases. Of these 49 subjects, 33 (67.3%) reported no prior sexual intercourse. Bacterial vaginosis was rare and 90% of subjects had a normal Nugent score (0-3). Conclusions Upon baseline evaluation of a cohort of low risk AGYW, we found high numbers of STIs, especially CT, which is not routinely screened for in Kenyan settings. Interventions to address STIs and unintended pregnancy should target girls pre-sexual debut, including those who do not self-identify as at risk.